Effect of soil amelioration on high value vegetables grown under protected conditions - VERMA, VEERENDRA KUMAR; CHOUDHURY, B U; JHA, ANJANI KUMAR (The Indian Journal of Agricultural Sciences, 2022)
High-value vegetable production under open field in northeast India’s hilly ecosystem often suffers from abiotic and biotic stresses (low temperature, soil acidity and moisture deficit during winter, and infestation of pests-diseases during humid summer). Protected cultivation with soil ameliorative measures may help in overcoming these limitations while sustaining year-round production. An experiment was conducted at the Horticulture Experimental Farm, ICAR Research Complex for NEH Region, Meghalaya for three consecutive years (2016–18) to study the yield performance of 4 high-value vegetables (tomato, capsicum, king-chilli and cucumber) grown under naturally ventilated polyhouse in the strong acid soils (pH<4.80) of mid-altitude (960 m amsl) sub-tropical hilly ecosystem of northeast India. Crops were grown with three ameliorative measures (liming @2.5 q/ha, black polythene mulching, and both) and yields were compared with control (without liming and mulching). Liming increased soil pH by 0.39–0.5 units, available phosphorus by 3.8–4.6 kg/ha and bases (calcium and magnesium) by 1.0–1.2 meq/100 g soil. On black polythene mulching, temperature (air and soil) increased by 5.5–8.7°C and 3.9–5.8°C, respectively, during extremely cold periods (December–February). Soil moisture retention was 3.8–5.2% higher over control plots. Ameliorative measures (liming or mulching) increased tomato yields by 15.0–28.5%, capsicum by 21.1–59.9% and king-chilli by 5.76–24.5% while cucumber yield in mulched plot increased 2-fold over respective control plots. The yields of all the vegetables further increased on the combined application of lime and mulch together. Findings suggest ameliorative measures promises better productivity of vegetables under controlled environment.